2022
DOI: 10.1101/2022.03.05.482955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cilia regulate meiotic recombination in zebrafish

Abstract: Meiosis is essential for evolution and genetic diversity in almost all sexual eukaryotic organisms. The mechanisms of meiotic recombination, such as synapsis, have been extensively investigated. However, it is still unclear whether signals from the cytoplasm or even outside of the cell can regulate the meiosis process. Cilia are microtubule-based structures that protrude from cell surface and function as signaling hubs to sense extracellular signals. Here, we reported an unexpected and critical role of cilia d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Our results demonstrate that zygotene cilia in mouse spermatocytes contain acetylated Tubulin -AcTub-, similarly to the zygotene cilia in zebrafish spermatocytes and oocytes [36,37].…”
Section: Meiotic Centrosomes and Their Relation To Ciliogenesis And F...mentioning
confidence: 53%
See 4 more Smart Citations
“…Our results demonstrate that zygotene cilia in mouse spermatocytes contain acetylated Tubulin -AcTub-, similarly to the zygotene cilia in zebrafish spermatocytes and oocytes [36,37].…”
Section: Meiotic Centrosomes and Their Relation To Ciliogenesis And F...mentioning
confidence: 53%
“…This provides a scenario that challenges the assumption that primary cilia are antagonistic with cell division, as it has to be taken into account that cells at zygotene have already started meiotic cell division [49]. Apart from our work and the recent advances in zebrafish gametogenesis [36, 37], another previous report also pointed at the presence of primary cilia during D. melanogaster spermatogenesis. Moreover, they suggested that these cilia were stable through both meiotic divisions in dividing spermatocytes with yet unknown functions [50].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations